INDIRECT PROMISING ACT PERFORMED BY THE CANDIDATES ON JAKARTA MEMILIH: THE FINAL ROUND AT DEBATE PROGRAM ON METRO TV - NIKMAH, NIKMATUN (Jurnal Ilmiah Mahasiswa FIB, 2013)
Jakarta as a capital city becomes the central of Indonesian goverment, business etc. Here, the candidates of Jakarta’s governors and vice governors involved in showing off their programs,  mission  and vision  to Jakarta’s  citizens.  As public politicians,   they   have   their   own   way   for   delivering   their intention such to do a promise. The purposes of this study are help  the  to  find  out  about  the  way  indirect  promising  act expressed by the candidates while also find out the implicit meaning of promising act. This research examines the transcript from the candidates. The data are utterances containing indirect promises that are produced by the candidates at debate program entitled  “Jakarta  Memilih:  The  Final  Round  on  Metro  TV” that’s  held on 16 September  2012.  This research  reveals  that there are 25 utterances include in indirect promising acts. From those findings, the researcher finds 23 utterances realized in declarative sentences and the other uses imperative and exclamative sentences. Besides, the researcher also finds 18 data of 25 utterances fulfill the condition of promising acts and 7 data do not fulfill the condition of promising act. Kata Kunci: Tindak Tutur, Janji Tak Langsung, Kondisi Janji, Jakarta Memilih: The Final Round di Metro TV